A urate gene-by-diuretic interaction and gout risk in participants with hypertension: results from the ARIC study. Issue 5 (29th June 2012) - McAdams-DeMarco, Mara A; Maynard, Janet W; Baer, Alan N; Kao, Linda W; Kottgen, Anna; Coresh, Josef
Abstract : Objective: To test for a urate gene-by-diuretic interaction on incident gout. Methods: The Atherosclerosis Risk in Communities Study is a prospective population-based cohort of 15 792 participants recruited from four US communities (1987–1989). Participants with hypertension and available single nucleotide polymorphism (SNP) genotype data were included. A genetic urate score (GUS) was created from common urate-associated SNPs for eight genes. Gout incidence was self-reported. Using logistic regression, the authors estimated the adjusted OR of incident gout by diuretic use, stratified by GUS median. Results: Of 3524 participants with hypertension, 33% used a diuretic and 3.1% developed gout. The highest 9-year cumulative incidence of gout was in those with GUS above the median and taking a thiazide or loop diuretic (6.3%). Compared with no thiazide or loop diuretic use, their use was associated with an OR of 0.40 (95% CI 0.14 to 1.15) among those with a GUS below the median and 2.13 (95% CI 1.23 to 3.67) for those with GUS above the median; interaction p=0.006. When investigating the genes separately, SLC22A11 and SLC2A9 showed a significant interaction, consistent with the former encoding an organic anion/dicarboxylate exchanger, which mediates diuretic transport in the kidney. Conclusions: Participants who were genetically predisposed to hyperuricaemia were susceptible to developing gout when taking thiazide or loop diuretics, an effect not evident among those without a genetic predisposition. These findings argue for a potential benefit of genotyping individuals with hypertension to assess gout risk, relative in part to diuretic use.